Analysis of the Influence of Work Stress and Work Life Balance on Worker Performance: Case Study of Sugio Lamongan Faizam Concrete Workers by Mediating Work Family Conflict - Eka Dewi Saputri; Lilik Nurcholidah (RTTM, 2025)
The purpose of this study is to determine the effect of work stress on work life balance on worker performance as a mediating variable of work family conflict using PLS-SEM (case study on faizam beton sugio lamongan workers). the type of research used is quantitative research. the population in this study sample amounted to 40 respondents in faizam beton workers. data collection in this study used the location survey method and questionnaire distribution. the data analysis technique used is PLS (partial least square) using supporting instruments, namely SmartPLS4 sofare. The results of the direct influence study indicate that work stress has a positive and significant effect on worker performance. Work stress has a positive and significant effect on work family conflict. Work life balance has a positive and significant effect on worker performance. Work life balance has a negative and significant effect on work family conflict. Work family conflict has a negative and insignificant effect on worker performance. Work Stress Has a Positive and Significant Effect on Work Family Conflict Through Worker Performance Faizam Beton Sugio Lamongan.